1991
DOI: 10.1002/ar.1092300404
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on cytochrome oxidase activities during denervation and recovery of three muscle fiber types

Abstract: The rat nasolabialis muscle is comprised of a mosaic of red, white, and intermediate muscle fiber types. Using computerized microdensitometry, cytochrome oxidase (COX) activity was quantitatively analyzed in each fiber type throughout the period of denervation and recovery in young adult (3-month) and middle-aged (15-month) male Sprague-Dawley rats. In animals of both age groups, the nasolabialis muscle on one side of the head was denervated by crushing the facial nerve. At specific days post crush (dpc) rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These changes lead to more glycolytic metabolism in red muscles. In the recovering muscle during reinnervation, the fiber types are transformed back into more oxidative, the activity of oxidative enzymes increases and the muscle shifts back to more oxidative metabolism (6,8,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes lead to more glycolytic metabolism in red muscles. In the recovering muscle during reinnervation, the fiber types are transformed back into more oxidative, the activity of oxidative enzymes increases and the muscle shifts back to more oxidative metabolism (6,8,38).…”
Section: Discussionmentioning
confidence: 99%
“…skeletal muscle; denervation; reinnervation PERIPHERAL NERVE CRUSH leads to functional denervation of muscles with a variety of degenerative changes in muscle morphology and biochemistry that subsist until the regeneration of injured nerve takes place. The changes include an immediate loss of muscle activity followed by atrophy and degeneration of muscle fibers, a decrease in mitochondrial oxidative enzyme activities, and a fall in high-energy phosphate contents (6,8,21,38). Reinnervation and regeneration of skeletal muscles result in restoration, to some degree, of the original muscle fiber structure and contractile activity accompanied by a reversal of some previous biochemical alterations (8,12,24,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bars=20 μm after SD rat sciatic nerve injury. Previous researches have shown that pathological changes in peripheral nerve system including damages, inflammation, tumor and denaturation could result in acute, subacute or chronic denervation, which is in turn responsible for the atrophy of target muscles [5,34]. But the molecular mechanisms of muscular atrophy, due to denervation remain to be elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…However, many studies only accessed 2 age groups, i.e. young and adult or young and old animals, to investigate the age-related variations [38,78,79]. The alterations that occur in skeletal muscle during different stages of aging, i.e.…”
Section: Discussionmentioning
confidence: 99%